Determining the general and academic vocabulary size of bachelor of Business Administration students / Farah Nadiah Mohammed Asrin - Mohammed Asrin, Farah Nadiah (Faculty of Education, 2011)
This research was conducted to identify the general and Academic word level of part one students in the Bachelor of Business Administration (BBA) part one students. In addition, this study tried to investigate whether there was any significant relationship between types of former education attended and samples’ vocabulary size, and between grades obtained in SPM English language paper and vocabulary size. A total of 114 BBA part one students in UiTM Melaka City Campus were invoved in this study as the respondents. Students’ General and Academic vocabulary size were tested using Schmitt, N., Schmitt, D. and Clapham’s (2001) Vocabulary Levels Test, in particular Version 1. The research findings showed that The BBA part one students could not be placed in any word level as their vocabulary size were inadequate at all word levels. Former Matriculation students resulted higher number of students who achieved the mastery level at the 2K, 3K and Academic word level. It was also found that the former education attended and grade obtained in the SPM English language paper have significance different in relation to the vocabulary size of the Bachelor programme students. From the findings, the researcher has come out with a few pedagogical implications for English language teachers towards the importance of assessing vocabulary of second language learners.